The Bio-herbicidal potential of some wild plants with allelopathic effects from Tabuk Region on selected local weed species - Alanaz, Amjad R.; Alatawi, Eman A. S.; Alotaibi, Rahaf S.; Alatawi, Eman A. H.; Albalawi, Attaf D.; Alhumayri, Hadeel A.; Alatawi, Qasem S.; Alharbi, Basmah M. (Frontiers in Plant Science, 2023)
Weeds are considered one of the most serious problems limiting global agricultural production. As a result, chemical herbicides have been extensively used for weed control. However, Overuse overuse of synthetic herbicides, however, has resulted in public concerns over the effect of herbicides on the health of the ecosystems and humans. In the food system, innovative approaches are needed to foster sustainable practices that preserve biodiversity, conserve habitats, and mitigate climate change factors. Thus, alternatives are required to control the weeds. This study aimed to determine the impact of some wild plants' (Citrullus colocynthis, Euphorbia retusa, Retama raetam, Artemisia monosperma, Tamarix gallica, and Artemisia Jjudaica) allelopathic potentials (at rates of 0, 15, 25, 35, and 50 g/L) on seed germination of selected local weeds (Portulaca oleracea, Amaranthus retroflexus, and Chloris barbata) collected from different locations in Tabuk region, Saudi Arabia. GC-MS analysis was used to evaluated the main compounds in the wild plants under study. A renowned taxonomist authenticated all specimens (donor plants and receptor plants). The experimental design was completely randomized block design (CRBD) with three replicates. According to the results, phytochemical screening of the wild plants using GC-MS analysis showed a wide range of phytochemicals. Amaranthus retroflexus exhibited the highest germination rate in the control group. In addition, applying 5 gm/L and 20 gm/L of Citrullus colocynthis extracts had no discernible effect on the rate of germination of A. retroflexus seed; however, they were able to reduce the germination rate as compared to the control. As the extract concentration of Artemisia monosperma rose to 20 gmg/L, the germination rate of A. retroflexus dropped. The control had the highest germination rate, and nNeither 35 gmg L-1 nor 50 gmg L-1 of A. monosperma extract caused inhibited the germinate of A. retroflexus to germinate. The germination rate of Portulaca oleracea decreased with increasing extract concentration of C. colocynthis. The control had the highest germination rate of P. oleracea, whereas tThe extract of C. colocynthis at 50 gmg/L had the lowest rate.